2021
DOI: 10.1186/s12885-021-09053-3
|View full text |Cite
|
Sign up to set email alerts
|

Elective neck dissection improves the survival of patients with T2N0M0 oral squamous cell carcinoma: a study of the SEER database

Abstract: Background Treatment of clinical N0 neck tumours is controversial in early-stage oral squamous cell carcinoma (OSCC), possibly because T1N0M0 and T2N0M0 merge together at early stages. The purposes of this study were to compare survival outcomes only for T2N0M0 cases based upon treatment elective neck dissection versus neck observation. Methods T2N0M0 OSCC cases were identified in the Surveillance, Epidemiology, and End Results database of the Unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…The SEER study of cT2N0M0 OCSCC staged in accordance with the AJCC Seventh Edition found, in contrast to the current investigation, that there was a roughly 10% difference in the 5‐year DSS rate between those who received NO and those who underwent END. As a result, in order to manage cT2N0M0 OCSCC, the SEER investigators recommended using END 7 . It is generally expected that, the differences in DSS between patients undergoing END and those receiving NO are anticipated to decrease in proportion to the prevalence of occult cervical metastases.…”
Section: Discussionmentioning
confidence: 99%
“…The SEER study of cT2N0M0 OCSCC staged in accordance with the AJCC Seventh Edition found, in contrast to the current investigation, that there was a roughly 10% difference in the 5‐year DSS rate between those who received NO and those who underwent END. As a result, in order to manage cT2N0M0 OCSCC, the SEER investigators recommended using END 7 . It is generally expected that, the differences in DSS between patients undergoing END and those receiving NO are anticipated to decrease in proportion to the prevalence of occult cervical metastases.…”
Section: Discussionmentioning
confidence: 99%
“…15 An important concern in early-stage OSCC is the presence of lymph node metastasis (clinically detected or occult), representing a major source of recurrence and cancer-related death. 16 Although occult lymph node metastasis is found in up to 30% of the OSCCs, the fear of its devastating effects often leads to elective dissection of the neck in early-stage OSCCs, mainly in those located in the tongue, causing overtreatment in many cases, with more adverse effects and higher financial burden than what is required. 17,18 In this context, it is essential to identify reliable biomarkers to accurately identify patients with a more aggressive tumor, in whom a complex therapy is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery remains the mainstay of treatment, including neck dissection for involved cervical lymph nodes as well as for staging the disease and access during reconstructive surgery 15 . An important concern in early‐stage OSCC is the presence of lymph node metastasis (clinically detected or occult), representing a major source of recurrence and cancer‐related death 16 . Although occult lymph node metastasis is found in up to 30% of the OSCCs, the fear of its devastating effects often leads to elective dissection of the neck in early‐stage OSCCs, mainly in those located in the tongue, causing overtreatment in many cases, with more adverse effects and higher financial burden than what is required 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] The elective neck dissection is the gold-standard method for early-stage tumors with clinically negative cervical lymph nodes. 20 However, this approach promotes postoperative morbidities and complications, and many patients undergoing this procedure have pathological confirmation of the absence of lymph node metastasis. 21 Therefore, an accurate, quick, and easy-to-detect biomarker could be a useful tool to assist physicians during the cervical dissection decision.…”
Section: Introductionmentioning
confidence: 99%
“…The elective neck dissection is the gold‐standard method for early‐stage tumors with clinically negative cervical lymph nodes 20 . However, this approach promotes postoperative morbidities and complications, and many patients undergoing this procedure have pathological confirmation of the absence of lymph node metastasis 21 .…”
Section: Introductionmentioning
confidence: 99%